From Conventional to Precision Therapy in Canine Mammary Cancer: A Comprehensive Review - Valdivia, Guillermo; Alonso-Diez, Ángela; Pérez-Alenza, Dolores; Peña, Laura (Frontiers in Veterinary Science, 2021)
Canine mammary tumors (CMTs) are the most common neoplasm in intact female dogs. Canine mammary cancer (CMC) represents 50% of CMTs and, besides surgery which is the election treatment, additional targeted and non-targeted therapies could offer benefits in terms of survival to these patients. Also, CMC is considered a good spontaneous intermediate animal model for the research of human breast cancer (HBC) and, therefore, the study of new treatments for CMC is a promising field in Comparative Oncology. Dogs with CMC have a comparable disease, an intact immune system, and a much shorter lifespan which allows the achievement of results in a relatively short time. Besides conventional chemotherapy, innovative therapies have a large niche of opportunities. In this article, a comprehensive review of the current research in adjuvant therapies for CMC is conducted to gather the available information and evaluate the perspectives. Firstly, by updating the clinical-pathological approach and the use of conventional therapies, to delve later into precision therapies against therapeutic targets such as hormone receptors, tyrosine kinase receptors, p53 tumor suppressor gene, cyclooxygenases, the signaling pathways involved in the epithelial-mesenchymal transition and immunotherapy in different approaches. A comparison of the different investigations on targeted therapies in HBC is also carried out. In the last years, it is outstanding the increasing number of basic research studies of new promising therapeutic agents on CMC cell lines and CMC mouse xenografts. As the main conclusion of this review, the lack of efforts to bring the in vitro studies to the field of applied clinical research emerges. There is a great need of well-planned large prospective randomized clinical trials in dogs with CMC to obtain valid results for both species, humans and dogs, on the use of new therapies. Following the One-Health concept, Human and Veterinary Oncology have to join forces to take advantage of both the economic and technological resources that are invested in HBC research, together with the innumerable advantages of dogs with CMC as a spontaneous animal model.